Conflict of Laws as Constitutional Form: Reflections on International Trade Law and the Biotech Panel Report - Joerges, Christian (Social Science Research Network, 2007)
Hardly anywhere is the trend towards a perfection of transnational governance arrangements and their “legalization” more visible than in international trade. Governance arrangements established through and alongside WTO law are both practically important and theoretically challenging. They do not just organise international trade relations. They also affect national and regional (European) regulatory policies partly directly, partly more indirectly. How can we explain and how should we evaluate their emergence? The WTO system of 1994, which replaced the GATT of 1947, responded to the ever increasing importance of non-tariff barriers to trade. These barriers reflect regulatory concerns especially in the fields of health and safety, consumer and environmental protection. There importance for WTO member is such that they cannot simply be abandoned for the sake of free trade. This is why the responses the new international trade system institutionalised by special agreements concerning on-tariff barriers to free trade such as the Agreement on the Application of Sanitary and Phytosanitary Measures (SPS) and the Agreement on Technical Barriers to Trade (TBT) reflect a politicisation of international trade. Can we conclude that international markets have been re-regulated and that international trade law ensures their “social embeddedness”? The paper seeks yardsticks for an answer to these questions in the debates on transnational constitutionalism. It submits that constutionalisation can and should be based on a conflict-of approach. For its elaboration of this suggestion, the paper first contrasts the jurdification of transnational governance at the European and the international level. It then discusses the WTO panel report on the Biotech dispute. It concludes that the legalisation and judicialisation in that case have remained “thin.” What can be observed is a political rather than a social and legal embeddedness of markets.
Law; Political Science
Keywords: FOUCAULT; Michel; 1926-1984; Polanyi and Foucault; World Trade Organization (WTO); constitutionalisation; economic law; embeddedness; european governance; international trade; legal embeddedness; legalization; legitimacy; multilevel governance; national autonomy; risk regulation; social embeddedness; transnational governance

Tanzanite: Commodity Fiction or Commodity Nightmare? - Donahue, Katherine Curtis (Social Science Research Network, 2007)
Karl Polanyi's discussion of the commodification of land, labour, and money is useful in analysis not only of nineteenth century markets but also of twenty-first century social and economic developments. This working paper explores the process of commodification of tanzanite, a gemstone discovered in the 1960s south of Mt. Kilimanjaro, Tanzania, and actively mined only since the 1980s. More rare than diamonds because the source area is limited to the Mererani hills east of Arusha, the gemstones reach markets through Maasai middlemen, foreign buyers, processors, cutters, polishers and dealers in Tanzania, India, Hong Kong, and the United States. The U.S. is responsible for 80% of the market for tanzanite. Production of the stone is occasionally slowed by flooding, accidents, and conflict over rights to mining areas. Children and teenagers often work in the tanzanite mines. These miners suffer death and disease not only because of unsafe mine conditions but also because of drug use and HIV/AIDS. Furthermore, this new commodity received close scrutiny after the attacks of September 11, 2001, because of a Wall Street Journal report that members of al Qaeda bought tanzanite for use in funding its networks and activities. This paper explores policy issues raised not only by that report and by global NGOs such as Global Witness, but also by the Tanzanian state, by health and safety workers and the miners and mining companies at Mererani. The paper is based on field interviews with buyers and sellers, in Tanzania and in the United States, as well as analysis of media reports, in order to argue that this particular commodity is, in Polanyi's terms, a fiction, one which has serious policy, social, health, and economic implications.
Anthropology
Keywords: Tanzania; Tanzanite; fictitious commodities; mining

The Great Transformation of Embeddedness: Karl Polanyi and the New Economic Sociology - Beckert, Jens (Social Science Research Network, 2007)
I argue that in its adaptation from Karl Polanyi’s The Great Transformation, the concept of embeddedness has itself undergone a great transformation. In the process, significant meanings of the concept have vanished, while others have been added. First I explore the different meanings the concept of embeddedness has achieved in the new economic sociology. Then I argue that it is not the embeddedness of economic action that should constitute the vantage point of economic sociology, but rather three coordination problems that actors face in economic exchange: the valuation of goods, competition and the problem of cooperation deriving from the social risks of exchange. I show that by proceeding from these coordination problems economic sociology, economic anthropology and economic history can find common research questions which allow them to enter into dialogue with each other more systematically. In the next section I focus on the social-reformist inclinations of Polanyi’s use of the notion of embeddedness and thereby highlight a challenge posed in The Great Transformation that was largely not taken up by economic sociologists. Finally, I discuss limitations for developing a macro theory of the economy that result from making embeddedness the core concept of economic sociology.
Sociology
Keywords: economic history; economic sociology; embeddedness; political economy